ASSESSMENT OF THE kNOWLEDGE, ATTITUDE AND PRACTICE OF RESIDENTS AT TIkUR ANBESA HOSPITAL ABOUT PRECONCEPTIONAL CARE 2018 - Seman, Wolela Alemu; Teklu, Sisay; Tesfaye, Kiflom (Ethiopian Journal of Reproductive Health, 2019)
ABSTRACT BACkGROUND: Preconception care is a set of interventions provided before pregnancy to identify and modify biomedical, behavioral, and social risks to a woman’s health or pregnancy outcome through prevention and management. OBJECTIVE: The aim of the study was to assess the knowledge, attitude and practice of physicians in Tikur Anbesa hospital about preconceptional care with the view of providing recommendations to optimize the uptake and delivery of the service and improve maternal and perinatal outcomes. METHODS: A descriptive cross-sectional study was done among 156 internal medicine and obstetrics and gynecology residents of Tikur Anbesa hospital using a self-administered semi structured questionnaire. The data was analyzed using descriptive statistics, chi-square and T-tests. P-value of less than 0.05 was taken as significant. RESULT: Of 156 questionnaires distributed 130 completed responses were collected making response rate of 83.3%. Among the respondents 69.2% had good, 26.9% had moderate and 3.8% had poor knowledge about preconceptional care. Of all the respondents 48.5% had positive, 43.8% had intermediate and only 7.7% had negative attitude towards preconceptional care. But only 19.2% of them had good practice scores, whereas 42.3% had moderate and 38.5% had poor preconceptional care practice scores. CONCLUSION: Even though the knowledge and attitude about preconceptional care is good there is a significant gap in the delivery of the services. Efforts should be made by the concerned bodies to improve the practice of preconceptional care through preparation of guidelines, providing training and creating awareness in the public. kEY WORDS: Preconception care, Tikur Anbesa hospital, Residents, KAP (Ethiopian Journal of Reproductive Health; 2019; 11;1:19-28